Social capital as a means of improving the quality of life of the elderly population (Regional aspects of productive forces development of Ukraine, 2020)
AbstractIntroduction. Access to social capital allows older people to lead productive, independent and fulfilling lives. Thus, the study of the importance of social capital in an aging population acquires special significance. It identified tasks, among which one of the main is to develop tools and conduct a survey on the level of social capital among the elderly in Ukraine, including from the standpoint of quality of life.Goal. The aim of the article is to substantiate the theoretical and applied aspects of assessing the role of social capital in improving the quality of life of the elderly population. Social capital is one of the resources that can be used to improve the quality of life in old age.Research methods. To solve this scientific problem, structural methods, comparative analysis, empirical data, abstract-logical generalization, statistical and sociological methods were used.Results. The article analyzes current trends, changes in the gender and age structure of the population and assesses the level of population aging compared to other countries. Approaches to the essence of social capital, its components are generalized. A methodology was developed and a sociological survey of elderly people was conducted (250 respondents from Ternopil region were interviewed. The sample was random, stratified by gender and type of settlement). The survey found that older people with strong family, cultural and social ties value their quality of life higher and have better health than people who are socially isolated. It is also important to have access to communication channels, in particular the Internet, which remains insufficient in Ukraine.Conclusions. The consequences of aging are already significant for the Ukrainian economy, which is unable to meet the needs of an aging population. One of the priority areas that will improve the quality of life of older people is the development of social capital. The results of the author's sociological study confirmed that active social connections and social contacts are important for the psychological health of the elderly. However, many of them are single with low social involvement and need social assistance (material and moral).